2011
DOI: 10.1002/mc.20844
|View full text |Cite
|
Sign up to set email alerts
|

Green tea catechin extract in intervention of chronic breast cell carcinogenesis induced by environmental carcinogens

Abstract: Sporadic breast cancers are mainly attributable to long-term exposure to environmental factors, via a multi-year, multi-step, and multi-path process of tumorigenesis involving cumulative genetic and epigenetic alterations in the chronic carcinogenesis of breast cells from a non-cancerous stage to precancerous and cancerous stages. Epidemiologic and experimental studies have suggested that green tea components may be used as preventive agents for breast cancer control. In our research, we have developed a cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 64 publications
0
37
0
Order By: Relevance
“…Green tea is a dietary plant that contains an important source of polyphenols and next to water, it is the second most commonly consumed beverage in the world after black tea, produced mainly from a single plant species Camellia sinensis [13][14][15]. Green tea has potential beneficial effects such as solar ultraviolet protection, antimutagenic, antidiabetic, antiinflammatory, anticancer, antioxidant, and immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Green tea is a dietary plant that contains an important source of polyphenols and next to water, it is the second most commonly consumed beverage in the world after black tea, produced mainly from a single plant species Camellia sinensis [13][14][15]. Green tea has potential beneficial effects such as solar ultraviolet protection, antimutagenic, antidiabetic, antiinflammatory, anticancer, antioxidant, and immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous reports, we demonstrated that GTCs, at non-cytotoxic levels, were capable of suppressing breast cell carcinogenesis induced by NB or PhIP [33][35]. EGCG, the major catechin present in green tea extract, is the most commonly studied preventive GTC [44], but some studies have shown that ECG may be more effective than EGCG in intervention of carcinogenesis [34], [45], [46].…”
Section: Resultsmentioning
confidence: 98%
“…Cellular studies have shown that EGCG and GTE protect against smoke-induced cellular proliferation [62, 71, 77], DNA damage [66, 80, 83], oxidative stress [22, 62, 71], and tumorigenesis [56, 71] through cell signaling pathways [71, 77]. More specifically, Syed et al reported that EGCG pretreatment (20–80 μM) of normal human bronchial epithelial cells (NHBE) resulted in significant inhibition of cigarette smoke condensate (CSC)-induced cell proliferation [77].…”
Section: Green Tea Modulates Smoke Related Diseases or Damagementioning
confidence: 99%
“…Aside from inhibiting smoke-induced cellular proliferation in normal cells, green tea polyphenols, such as GTP, EGCG, ECG, EGC, and EC, also reduced smoke-induced DNA damage [66, 71, 80]. Pretreatment with 20–100μg/mL GTP for 2 h resulted in a dose-dependent decrease in smoke-mediated DNA damage in A549 cells, and GTP concentration was inversely correlated with the extent of DNA damage observed [66].…”
Section: Green Tea Modulates Smoke Related Diseases or Damagementioning
confidence: 99%